Analysis of USA swimming's all-time Top 100 times - Sokolavas, G. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to investigate the performances of elite level swimmers based on the USA Swimming's All-Time Top 100 times. We analyzed participation of 17-18 years old swimmers at Top 100 from age 10-under until the age of 15-16 years in various events by girls and boys. The data shows that the older the elite swimmer, the more likely he/she will be ranked in the Top 100. About half of the elite swimmers in the Top 100 at age 17-18 were new swimmers who were never ranked in the Top 100 at any age. Most of the future elite swimmers swim slower than age group Champions, especially at ages until 15-16 years. Many participant ranked in the Top 100 as age groupers are not present in the Top 100 in the 17-18 age group. We speculate that the two reasons for losing these young Top 100 ranked Champions may be related to their early biological maturation and/or an inappropriate training volume at a young age.